Behind the Decrease of Liver Stiffness After Successful Hepatitis C Virus Eradication with Direct-Acting Antiviral Agents - Giuffrè, Mauro; Masutti, Flora; Crosato, Ivo Maria; Luzzati, Roberto; Crocè, Lory Saveria (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Giuffrè M, Masutti F, Maria Crosato I, Luzzati R, Saveria Crocè L. Behind the decrease of liver stiffness aftersuccessful hepatitis c virus eradication with direct-acting antiviral agents. Turk J Gastroenterol. 2021;XX:1-2.